Garden of Mission San Buenaventura - Les Stephens::::::photographer::: (Canoga Park Photography Center)
Back of postcard reads: 'Shrine of Our Mother of Grace in the garden of Mission San Buenaventura, founded by Father Junipero Serra in 1782.'